PENERAPAN METODE ACCELERATED LEARNING FOR THE 21st CENTURY DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA - Herianto Herianto (Delta: Jurnal Ilmiah Pendidikan Matematika, 2019)
This research is a class action research (Classroom Action Research) aimed at improving the learning outcomes of students of student mathematics VIIIA MTs Darul I'tisham Embo Tamalatea subdistrict of Jeneponto district through the application of the Accelarated method Learning for the 21st Century. The subject of research is 33 students of the class VIIIA MTs Darul I'tisham Embo Tamalatea Sub-district of Jeneponto District lesson 2018/2019.Studies have been conducted in two cycles. Each cycle is carried out as many as three meetings including the test end of the cycles. Data retrieval is carried out using observations and test descriptions. The Data obtained is analyzed using quantitative analysis and descriptive statistics.The results showed that student learning results of VIIIA MTs Darul I'tisham Embo Sub-district of Jeneponto subdistrict can be upgraded through the implementation of the method of Accelarated Learning for the 21st Century with a percentage of 87.89%. These results are categorized as high with the average value of student learning outcomes of 72.67. The observation shows the increasing frequency of students ' attendance and the activation of students in following the learning process. Thus, the implementation of the method of Accelarated Learning for the 21st Century can improve the learning outcomes of the class of VIIIA MTs Darul I'tisham Embo in Tamalatea Sub-district of Jeneponto.